Transport of the patient with trauma: a narrative review. (12th September 2022) - Spoelder, E. J.; Slagt, C.; Scheffer, G. J.; van Geffen, G. J.
Summary: Trauma and injury place a significant burden on healthcare systems. In most high‐income countries, well‐developed acute pre‐hospital and trauma care systems have been established. In Europe, mobile physician‐staffed medical teams are available for the most severely injured patients and apply a wide variety of lifesaving interventions at the same time as ensuring patient comfort. In trauma systems providing pre‐hospital care, medical interventions are performed earlier in the patient journey and do not affect time to definite care. The mode of transport from the accident scene depends on the organisation of the healthcare system and the level of hospital care to which the patient is transported. This varies from 'scoop and run' to a basic community care setting, to advanced helicopter emergency medical service transport to a level 4 trauma centre. Secondary transport of trauma patients to a higher level of care should be avoided and may lead to a delay in definitive care. Critically injured patients must be accompanied by at least two healthcare professionals, one of whom must be skilled in cardiopulmonary resuscitation and advanced airway management techniques. Ideally, the standard of care provided during transport, including the level of monitoring, should mirror hospital care. Pre‐hospital care focuses on the critical care patient, but the majority of injured patients need only close observation and pain management during transport. Providing comfort and preventing additional injury is the responsibility of the whole transport team.